The clinical utility of autoantibodies in systemic sclerosis: a review with a focus on cohort differences and standardization - Komura, Kazuhiro (Frontiers in Immunology, 2025)
BackgroundSystemic sclerosis (SSc) is clinically heterogeneous. Disease-specific autoantibodies—anticentromere (ACA), anti–topoisomerase I (ATA/Scl-70), and anti–RNA polymerase III (RNAP III)—are central to classification and organ-risk prediction. Beyond prognosis, SSc-specific autoantibodies can support diagnosis as part of a composite assessment with nailfold capillaroscopy and clinical features; their contribution is reflected in the 2013 ACR/EULAR classification criteria and can be informative in very-early or sine presentations. More broadly, these immune signatures underpin routine SSc care and underscore the immunological impacts that shape disease expression.MethodsNarrative review (2000–August 2025) prioritizing studies in Japanese and Western cohorts, with emphasis on assay performance and cohort comparability. We appraise line immunoassay (LIA) performance vis-à-vis immunoprecipitation (IP), and integrate ICAP-compliant ANA interpretation.ResultsACA aligns with lower ILD risk but higher PAH and digital vasculopathy; ATA predicts ILD onset/progression; RNAP III marks rapid skin thickening, SRC risk, and temporally clustered malignancy; U1 RNP tracks overlap/MCTD-like features and PAH; U3 RNP indicates diffuse disease with vasculopathy; Th/To varies by center; PM-Scl and Ku flag overlap ILD/myositis. A clinical-first standardized workflow—ANA (ICAP) + core ELISAs (ACA, ATA, RNAP III, U1 RNP) followed by ANA-pattern–guided LIA/IP confirmation—supports both care and cross-cohort comparability.ConclusionsAutoantibodies form a practical foundation for SSc care across regions. Standardizing the reflex layer (LIA/IP) while leveraging established ANA and core ELISAs can reduce measurement-driven cohort differences and improve global synthesis of SSc evidence.